Comparing the Efficacy of Endoscopic Carpal Tunnel Repair Versus Open Surgery: A Systematic Review and Meta-analysis of Randomized Control Trials - Yazeed A. Almojel; Hussam A. Alhathlol; Yazeed A. Asery; Nawaf K. Nahhas; Mohammed I. Alhumaidan, MBBS; Maan Almaghrabi, MBBS; Mohammed D. Alqarni, MBBS; Alaa Alsahli, MBBS; Turki S. Alhassan, MBBS (Plastic and Reconstructive Surgery, Global Open)
Background:. Surgical decompression of carpal tunnel syndrome by the standard open carpal tunnel release (OCTR) technique was associated with postoperative pain and tenderness. Thus, the endoscopic carpal tunnel release (ECTR) has been introduced to reduce the complications of open surgery through a shorter incision to decrease scar pain and achieve rapid recovery. In this study, we aimed to compare the outcomes between OCTR and ECTR, according to randomized controlled trial evidence. Methods:. A systematic literature search was conducted in PubMed, Web of Science, EBSCO, and Cochrane Central Register of Controlled Trials (CENTRAL) databases. Meta-analysis was performed using Comprehensive Meta-analysis software. Standard mean difference and a 95% confidence interval were used for continuous outcomes, whereas odds ratio with 95% confidence intervals were utilized for dichotomous outcomes. Results:. A total of 34 studies were included. ECTR has shown significant lower rates of scar pain and significant shorter recovery compared OCRT. However, we could not find any significant difference between the groups in terms of complication rates, incidences of local pain, mean pain scores, subjective complete or near complete symptom relief rate, subjective complete satisfaction rate, mean satisfaction scores, mean scores of symptom severity, mean scores of functional status, and mean time of operation. Conclusions:. Both ECTR and OCTR are safe and effective in management of carpal tunnel syndrome. However, ECTR may be slightly superior in terms of scar pain and postoperative recovery, although other factors not included in this study, including cost and convenience, must be considered.